Accuracy of Antibiotic Allergy Documentation and the Validity of Physicians’ Decision in a Pediatric Tertiary Care Setting - Al Jeraisy M (Dove Medical Press, 2021)
Majed Al Jeraisy,1,2 Shaden Al Osaimi,1 Abdullah Al Hawas,1 Alanoud Muamar,1 Lamia Aleidi,3 Njoud Khonain,4 Mostafa A Abolfotouh2 1College of Pharmacy, King Saud Bin Abdulaziz University for Health Sciences, Ministry of National Guard-Health Affairs, Riyadh, Saudi Arabia; 2King Abdullah International Medical Research Center, King Saud Bin Abdulaziz University for Health Sciences, Ministry of National Guard-Health Affairs, Riyadh, Saudi Arabia; 3Unaizah College of Pharmacy, Qassim University, Riyadh, Saudi Arabia; 4College of Pharmacy, Princess Noura Bint Abdulrahman University, Riyadh, Saudi ArabiaCorrespondence: Mostafa A AbolfotouhKing Abdullah International Medical Research Center (KAIMRC)/King Saud bin-Abdulaziz University for Health Sciences (KSAU-HS), Ministry of National Guard- Health Affairs, P.O. Box 3660, Riyadh, 11426, Saudi ArabiaTel +966 11 429-4460; +966 503659204Fax +966 11 429-4440Email mabolfotouh@gmail.comBackground: Patients allergic to antibiotics are at higher risk of receiving treatment with a broader spectrum, more harmful, and expensive agents. The aims of this study were (1) to assess the quality of documentation of antibiotics allergies in the electronic medical records (EMR) in a Pediatric tertiary care setting, and (2) to determine the validity of physicians’ decision to hold antibiotics prescriptions.Methods: This is a retrospective cohort study at King Abdullah Specialized Children Hospital, Riyadh, Saudi Arabia. A review of the EMR and all Adverse Drug Reaction (ADR) reports of pediatric patients 1– 14 years old, with a documented allergy to antibiotics from June 2016 until June 2019. The quality of documentation of antibiotics allergy was assessed based on the presence of four parameters: 1) allergy alert notification, 2) allergy severity classification, 3) setting notes, and 4) symptoms’ description. In addition, all physicians’ reports of allergy to antibiotics were cross-classified according to their corresponding ADR reports, and the validity of physicians’ documentation of allergy was assessed.Results: Of a total of 105 Pediatric patients’ EMR, documentation of antibiotics allergy was available in 98 (93.3%), with the presence of symptoms description (83%), allergy notes (87%), severity (67%), and signs of alert (50.8%). Overall documentation quality was good for only 23.5% of patients, while it was poor for 35.7%. Physicians’ documentation of antibiotics allergy was 0.82 sensitive [with 0.18 risk of allergy] and 0.60 specific [with 0.40 unnecessary restrictions of prescriptions]. Of all children with possible/actual allergies, only 38.9% were referred to the immunology clinic.Conclusion: The quality of documentation of antibiotic allergy in children and the validity of physicians’ decisions are less than satisfactory. Therefore, improving communications between all healthcare providers regarding patients’ allergy status and follow-up for further assessment of the reaction is recommended to improve patient care.Keywords: flagging, drug allergy, allergy documentation, quality, Naranjo scale